Human T-Cell Leukemia Virus Type 1 Tax Induction of NF-κB Involves Activation of the IκB Kinase α (IKKα) and IKKβ Cellular Kinases - Geleziunas, Romas (American Society for Microbiology, 1998)
Tax corresponds to a 40-kDa transforming protein from the pathogenic retrovirus human T-cell leukemia virus type 1 (HTLV-1) that activates nuclear expression of the NF-κB/Rel family of transcription factors by an unknown mechanism. Tax expression promotes N-terminal phosphorylation and degradation of IκBα, a principal cytoplasmic inhibitor of NF-κB. Our studies now demonstrate that HTLV-1 Tax activates the recently identified cellular kinases IκB kinase α (IKKα) and IKKβ, which normally phosphorylate IκBα on both of its N-terminal regulatory serines in response to tumor necrosis factor alpha (TNF-α) and interleukin-1 (IL-1) stimulation. In contrast, a mutant of Tax termed M22, which does not induce NF-κB, fails to activate either IKKα or IKKβ. Furthermore, endogenous IKK enzymatic activity was significantly elevated in HTLV-1-infected and Tax-expressing T-cell lines. Transfection of kinase-deficient mutants of IKKα and IKKβ into either human Jurkat T or 293 cells also inhibits NF-κB-dependent reporter gene expression induced by Tax. Similarly, a kinase-deficient mutant of NIK (NF-κB-inducing kinase), which represents an upstream kinase in the TNF-α and IL-1 signaling pathways leading to IKKα and IKKβ activation, blocks Tax induction of NF-κB. However, plasma membrane-proximal elements in these proinflammatory cytokine pathways are apparently not involved since dominant negative mutants of the TRAF2 and TRAF6 adaptors, which effectively block signaling through the cytoplasmic tails of the TNF-α and IL-1 receptors, respectively, do not inhibit Tax induction of NF-κB. Together, these studies demonstrate that HTLV-1 Tax exploits a distal part of the proinflammatory cytokine signaling cascade leading to induction of NF-κB. The pathological alteration of this cytokine pathway leading to NF-κB activation by Tax may play a central role in HTLV-1-mediated transformation of human T cells, clinically manifested as the adult T-cell leukemia.